Unleashing the secrets of academic writing: exploring Indonesian language courses in higher education - Kusmanto, Hari; Zamzani, Zamzani; Suryaman, Maman (Intelektual Pustaka Media Utama, 2024)
Academic writing has been a widely substantial course in higher education as it plays a vital role in cultivating students’ academic writing skills. Drawing on qualitative descriptive study, this study aims to explore the fundamental requirements for academic writing to base the creation of an effective learning framework. Data consisted of teaching materials, semester learning plan (SLP), assessment tools, and guidelines for academic writing from three universities in Surakarta, Central Java, Indonesia. Findings reveal that learning materials and the SLP have both strengths and weaknesses. Despite these, there is diversity in learning and assessment methods. Adopted teaching methods encompass project-based learning, problemsolving, and lectures, while learning assessment includes portfolio techniques, project assessment, and written exams. These findings provide insight into the imperative of academic writing in the academic setting. This serves as a basis for the development of more effective learning methods. Thus, the proposed model for academic writing adopts a project-based approach to improve students’ writing by integrating indigenous wisdom to promote students' character development.